Physiological response to anaerobicity of glycerol-3-phosphate dehydrogenase mutants of Saccharomyces cerevisiae. - Björkqvist, S (1997)
Mutants of Saccharomyces cerevisiae, in which one or both of the genes encoding the two isoforms of NAD-dependent glycerol-3-phosphate dehydrogenase had been deleted, were studied in aerobic batch cultures and in aerobic-anaerobic step change experiments. The respirofermentative growth rates under aerobic conditions with semisynthetic medium (20 g of glucose per liter) of two single mutants, gpd1 delta and gpd2 delta, and the parental strain (mu = 0.5 h-1) were almost identical, whereas the growth rate of a double mutant, gpd1 delta gpd2 delta, was approximately half that of the parental strain. Upon a step change from aerobic to anaerobic conditions in the exponential growth phase, the specific carbon dioxide evolution rates (CER) of the wild-type strain and the gpd1 delta strain were almost unchanged. The gpd2 delta mutant showed an immediate, large (> 50%) decrease in CER upon a change to anaerobic conditions. However, after about 45 min the CER increased again, although not to the same level as under aerobic conditions. The gpd1 delta gpd2 delta mutant showed a drastic fermentation rate decrease upon a transition to anaerobic conditions. However, the CER values increased to and even exceeded the aerobic levels after the addition of acetoin. High-pressure liquid chromatographic analyses demonstrated that the added acetoin served as an acceptor of reducing equivalents by being reduced to butanediol. The results clearly show the necessity of glycerol formation as a redox sink for S. cerevisiae under anaerobic conditions.